(untitled) - Cisterna Cahuer, Víctor; Sepúlveda Chavera, Germán F. (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Efficiency of an enzymatic detergent in the control of Praelongorthezia olivicola (Beingolea) (Hemiptera: Ortheziidae) in the Northern Chile (2015)

(untitled)
The efficiency of an enzymatic detergent (Nudisoit®) in the control of the mobile scale of the olive tree, Praelongorthezia olivicola (Hemiptera: Ortheziidae), was evaluated under laboratory and on-field conditions. In the laboratory test, four treatments and four repetitions were established in a completely randomized design; individuals surviving after 72 hours was evaluated. In the on-field test, the experimental design was completely randomized with four treatments and three repetitions; the treatments were done 7 days after the application, determining the degree of efficiency. The results indicates a higher control of the mobile scale under laboratory conditions, with an efficiency above 99%, both for nymphs and egg-laying females. On the field test, Nudisoit® exhibited levels of efficiency close to 74% on nymphs and 48% on egg-laying females. Both, the lower control of the plague and the variations observed on field are probably explained by deficiencies in the coverage, where the leaves acted to the detriment of the detergent, which principally acts by contact.